Efficacy and Safety of Rituximab in the Treatment of Idiopathic Membranous Nephropathy: A Meta-Analysis - Huijuan Lu; Jun Shen; Jieqiong Sun; Jia Sun (Applied Bionics and Biomechanics)
Background. Primary membranous nephropathy (MN), sometimes referred to as idiopathic membranous nephropathy (IMN), is a kind of MN whose pathogenesis is yet unclear. According to research reports, the incidence of IMN is about 9.8–26.8%, and it is on the rise. Methods. The computer retrieves eight databases to obtain controlled trials at home and abroad on the rituximab (RTX) actions in IMN management. After a rigorous literature quality evaluation, software called RevMan 5.3 was used for data analysis. Results. This meta-analysis finally contained 8 papers. They were all regarded as controlled trials. Six studies reported serum creatinine (standardized mean difference [SMD]: −6.87; 95% CI: −14.09, 0.35; P=0.062), ALB (SMD: 1.91; 95% CI: −0.31, 4.14; P=0.092), and adverse reactions (OR: 0.56; 95% CI: 0.36, 0.90; P<0.01), all of which were significantly higher in the test group than in the control group (OR: 1.37; 95% CI: 1.07, 1.76; P<0.01) Conclusion. The overall effective rate, serum creatinine, adverse effects, and ALB of this trial indicate that RTX may be beneficial for individuals with IMN, but further high-quality research is required to confirm these findings.